PHARMACOLOGICAL EFFICACY OF AN INHIBITOR OF ARGINASE-2 KUD975 WITH L-NAME-INDUCED ENDOTHELIAL DYSFUNCTION - Konstantin Kudryavtsev; Michael Korokin; Oleg Gudyrev (Belgorod National Research University, 2017)
The study of endotelio- and cardioprotective activity of finished dosage forms - tablets, film-coated, containing 10 mg of phenolic nature KUD-975, was shown a statistically significant decrease in blood pressure and the coefficient of endothelial dysfunction on the background of simulation L-NAME-induced pathology. In the group of animals treated with KUD975 found a statistically significant increase in the concentrations of stable metabolites of nitric oxide, which in addition to the normalization of vasodilation says about endothelioprotektive action of the compounds studied. The initial values of the functioning of the left ventricle of the heart during treatment with KUD975 found hypodynamic action, which resulted in a decrease in the absolute values of the heart left ventricle pressure, + dp / dt, -dp / dt. Results of the study of the functional state of the myocardium during exercise testing, and histological evaluation of the myocardium revealed distinct cardioprotective effects in the study of KUD975 at a dose of 3 mg / kg, expressed in preventing the increase adrenoreactivity, exhaustion myocardial reserve during the sample to the load resistance and hypodynamic restructuring physiological response to the report on hypoxia / reoxygenation compared with animals that have modeled the endothelial dysfunction.